Heterogeneity of proangiogenic features in mesenchymal stem cells derived from bone marrow, adipose tissue, umbilical cord, and placenta. Issue 1 (December 2016) - Du, Wen; Chi, Ying; Yang, Zhou; Li, Zong; Cui, Jun; Song, Bao; Li, Xue; Yang, Shao; Han, Zhi; Han, Zhong
Abstract Background Mesenchymal stem cells (MSCs) have been widely proven effective for therapeutic angiogenesis in ischemia animal models as well as clinical vascular diseases. Because of the invasive method, limited resources, and aging problems of adult tissue-derived MSCs, more perinatal tissue-derived MSCs have been isolated and studied as promising substitutable MSCs for cell transplantation. However, fewer studies have comparatively studied the angiogenic efficacy of MSCs derived from different tissues sources. Here, we evaluated whether the in-situ environment would affect the angiogenic potential of MSCs. Methods We harvested MSCs from adult bone marrow (BMSCs), adipose tissue (AMSCs), perinatal umbilical cord (UMSCs), and placental chorionic villi (PMSCs), and studied their "MSC identity" by flow cytometry and in-vitro trilineage differentiation assay. Then we comparatively studied their endothelial differentiation capabilities and paracrine actions side by side in vitro. Results Our data showed that UMSCs and PMSCs fitted well with the minimum standard of MSCs as well as BMSCs and AMSCs. Interestingly, we found that MSCs regardless of their tissue origins could develop similar endothelial-relevant functions in vitro, including producing eNOS and uptaking ac-LDL during endothelial differentiation in spite of their feeble expression of endothelial-related genes and proteins. Additionally, we surprisingly found that BMSCs and PMSCs could directly form tubular structures in vitro on Matrigel and their conditioned medium showed significant proangiogenic bioactivities on endothelial cells in vitro compared with those of AMSCs and UMSCs. Besides, several angiogenic genes were upregulated in BMSCs and PMSCs in comparison with AMSCs and UMSCs. Moreover, enzyme-linked immunosorbent assay further confirmed that BMSCs secreted much more VEGF, and PMSCs secreted much more HGF and PGE2. Conclusions Our study demonstrated the heterogeneous proangiogenic properties of MSCs derived from different tissue origins, and the in vivo isolated environment might contribute to these differences. Our study suggested that MSCs derived from bone marrow and placental chorionic villi might be preferred in clinical application for therapeutic angiogenesis.